The Effect of Facilities, Service Quality, and School Image on Parental Satisfaction at SD ABC Balikpapan - Mey Liana Tjan; Tin Agustina Karnawati; Teguh Widodo (Publikasi Indonesia, 2026)
This study aims to analyze the influence of school facilities, service quality, and school image on parental satisfaction at SD ABC Balikpapan. The research employed a quantitative approach using a survey method, with data collected through questionnaires distributed to parents or guardians of students. The research variables consisted of school facilities, service quality, and school image as independent variables, and parental satisfaction as the dependent variable. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that school facilities have a positive effect on parental satisfaction, service quality has a positive and significant effect on parental satisfaction, and school image has a positive and significant effect on parental satisfaction. These findings demonstrate that the provision of adequate facilities, high-quality educational services, and a positive school image play an important role in enhancing parental satisfaction. This study is expected to serve as a reference for school management in improving the quality of educational services and the management of school facilities.